Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am failing to understand the proof of coming to the steady-state formula in queueing theory. This is probably due to the fact that I may have forgotten (and cannot find it back) some of the algebra from my school days. The step I am missing is the transition from the first to the second statement below:

$$(\lambda + \mu)\frac{\lambda}{\mu}P_0 = \lambda P_0 + \mu P2$$

$$\frac{\lambda^2}{\mu}P0 + \lambda P_0 = \lambda P_0 + \mu P2$$

My main question is how does $$(\lambda + \mu)\frac{\lambda}{\mu}P_0$$ become $$\frac{\lambda^2}{\mu}P_0 + \lambda P_0$$ and what did happen to: $$\mu$$

Can anybody help me out?

share|cite|improve this question
up vote 2 down vote accepted

Recall the distributive law: If $a,b,c$ are terms, we have $(a+b)c=ac+bc$. In this case,

$$(\lambda+\mu)\frac{\lambda}{\mu}P_0 = \lambda\frac{\lambda}{\mu}P_0 + \mu\frac{\lambda}{\mu}P_0= \frac{\lambda \cdot \lambda}{\mu}P_0 + \frac{\mu \cdot \lambda}{\mu}P_0 = \frac{\lambda^2}{\mu}P_0 + \lambda P_0.$$

I hope this helps. Let me know if you need more detail.

share|cite|improve this answer
I recall that, but then you would expect that somewhere you get a value along the lines this would result in: $$\frac{\lambda^2}{\mu}P_0 + \lambda P_0 + \mu P_0$$ – Jochem May 12 '13 at 8:22
I'm sorry, I don't follow. Could you expand on your question a little bit? – Potato May 12 '13 at 8:24
@Jochem It might help to note that $\frac{\lambda}{\mu}P_0$ is one term and plays the role of $c$ in the distributive law. – Potato May 12 '13 at 8:26
This part I understand: $$(\lambda+\mu)\frac{\lambda}{\mu}P_0 = \lambda\frac{\lambda}{\mu}P_0 + \mu\frac{\lambda}{\mu}P_0$$ But when you add them up you get: $$\frac{\lambda * \lambda}{\mu}P_0 + \frac{\mu * \lambda}{\mu}P_0$$ Is it here that multiplying of the $$\mu$$ in the second part results in $$P_0$$? – Jochem May 12 '13 at 8:28
@Jochem That is correct. The first term you wrote at the bottom becomes $\frac{\lambda^2}{\mu}P_0$, and the second is $\lambda P_0$. Does this make sense? – Potato May 12 '13 at 8:32

This is rather simple actually, all you need to do is expand (distribute the elements).

Expanding this: $$ (\lambda + \mu)\frac{\lambda}{\mu}P0 $$

We have this: $$ \frac{\lambda^2}{\mu}P0+\frac{\mu\lambda}{\mu}P0 $$

And the final result after simplification is : $$ \frac{\lambda^2}{\mu}P0 + \lambda P0 $$

To answer your question about what happened to $\mu$. When you simplify: $\frac{\mu\lambda}{\mu}$ it becomes $1\lambda$, which is the same as just $\lambda$.

share|cite|improve this answer
Thank you. Just went through the same line of thought with @Potato. – Jochem May 12 '13 at 8:39

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.